1969
DOI: 10.1128/jb.97.1.256-260.1969
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Ferrobacillus ferrooxidans on Organic Matter

Abstract: Following a brief adaptation period to glucose, Ferrobacillus ferrooxidans was grown on glucose, mannitol, several other sugars, and a few amino acids in the absence of an oxidizable iron source. Prolonged growth on an organic substrate free from iron rendered the organism obligately organotrophic. The growth rate of the bacterium was greater in heterotrophic culture; the doubling time was approximately 4.5 hr on glucose. The bacterium retained its acidophilic properties during adaptation and growth on glucose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
23
0

Year Published

1971
1971
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(25 citation statements)
references
References 18 publications
2
23
0
Order By: Relevance
“…Two strains of T . ferrooxidans have been shown able to grow heterotrophical-Iy, and are thus "facultative autotrophs" (REMSEN and LUNDGREN 1963, LUND- GREN et al 1964, LUNDGREN 1969, SHAFIA and WILKINSON 1969. I n all work so far, successful culture on glucose as sole energy source required two or more "adaptation cultures", in which the bacteria were transferred in media containing both Fea+ and glucose (first a t 0.5y0, then a t 1 yo) before growth on 1 yo glucose MATIN and RITTENBERQ 1970, PEETERS et al 1970, CHARLES 1971, KELLY 1971.…”
Section: Silvermentioning
confidence: 99%
See 1 more Smart Citation
“…Two strains of T . ferrooxidans have been shown able to grow heterotrophical-Iy, and are thus "facultative autotrophs" (REMSEN and LUNDGREN 1963, LUND- GREN et al 1964, LUNDGREN 1969, SHAFIA and WILKINSON 1969. I n all work so far, successful culture on glucose as sole energy source required two or more "adaptation cultures", in which the bacteria were transferred in media containing both Fea+ and glucose (first a t 0.5y0, then a t 1 yo) before growth on 1 yo glucose MATIN and RITTENBERQ 1970, PEETERS et al 1970, CHARLES 1971, KELLY 1971.…”
Section: Silvermentioning
confidence: 99%
“…ferrooxidans are able t o grow a t the expense of sulphur and thiosulphate oxidation to sulphate (CDLMER 1962, LANDESMAN et al 1966, MARGALITH et al 1966. Generation times on sulphur generally fall in the range 10-25 hr (UNZ and LUNDGREN 1961, SILVER 1970), compared with 6.5-15 hr on iron (BECK 1960, MCGORAN et al 1969, SHAFIA and WILKINSON 1969. In some cases growth on sulphur or thiosulphate appears t o require a considerable adaptation period (UNZ and LUNDQREN 1961, JONES et al unpublished).…”
mentioning
confidence: 99%
“…T. ferrooxidans strain KG-4 was originally supplied by Dr. F. Shafia (California State Polytechnic College, Pomona, CA 91768) and maintained on glucose [5,6]. Growth experiments were carried out using 50 ml * Present addresses: Lumatek Ltd., P.O.…”
Section: Methodsmentioning
confidence: 99%
“…Thiobacillus ferrooxidans has been classified as a strict autotroph (15). However, Shafia et al (5,6) and Tabita and Lundgren (11) have shown that when autotrophically grown cells are transferred to a medium containing iron plus glucose, cells preferentially utilize ferrous iron, and when the iron is exhausted, they use glucose. These glucose-adapted cells can grow on glucose as the sole energy source upon transfer into a glucosesalts medium.…”
mentioning
confidence: 99%
“…These glucose-adapted cells can grow on glucose as the sole energy source upon transfer into a glucosesalts medium. Some conditions for adaptation and the enzymes involved in glucose metabolism have been studied by several workers (5,6,(11)(12)(13).…”
mentioning
confidence: 99%